2021
DOI: 10.1021/acs.biomac.1c01107
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Insulin Aggregation with Charge Variable Cholic Acid-Derived Polymers

Abstract: To understand the effect of cholic acid (CA)-based charge variable polymeric architectures on modulating the insulin aggregation process, herein, we have designed side-chain cholate-containing charge variable polymers. Three different types of copolymers from 2-(methacryloyloxy)ethyl cholate with anionic or cationic or neutral units have been synthesized by reversible addition-fragmentation chain transfer polymerization. The effects of these copolymers on the insulin fibrillation process was studied by multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…As a consequence, the formation of critical nuclei is hindered, which eventually stops the fibrillation. Our result is in accordance with our previous works, 7,11 where a decrease in the Tyr fluorescence intensity in the presence of polymers is considered a hallmark of the involvement of hydrophobic interactions. On the basis of the obtained results, we can conclude that the major driving force involved in inhibiting insulin aggregation is the hydrophobic interaction.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…As a consequence, the formation of critical nuclei is hindered, which eventually stops the fibrillation. Our result is in accordance with our previous works, 7,11 where a decrease in the Tyr fluorescence intensity in the presence of polymers is considered a hallmark of the involvement of hydrophobic interactions. On the basis of the obtained results, we can conclude that the major driving force involved in inhibiting insulin aggregation is the hydrophobic interaction.…”
Section: Resultssupporting
confidence: 94%
“…Thus, the design of novel therapeutic materials for the inhibition of amyloid aggregation stands as a major topic of research from the therapeutic point of view. 10,11 In this milieu, extensive efforts have been implemented to explore the effect of polymeric materials on the insulin aggregation process. 12,13 Fang and co-workers have reported the potential of polyethylene glycol-phosphatidylethanolamine (PEG-PE) micelles in suppressing the oligomerization and fibrillation of human islet amyloid polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the routine steady state and timeresolved emission studies in the ensemble level, we used fluorescence lifetime imaging microscopy (FLIM) to obtain more details on the process. The versatile FLIM technique has been used several times earlier to locate biologically important lipid rafts in model membranes, 40,41 to study the interaction of biologically essential dyes in lipid vesicles, 42,43 in the preparation of fluorescent polymeric thermometers, 44 in monitoring fibril disintegration of insulin in the presence of cholic acid polymer 45 and also for protein sensing. 46,47 However, studies on CDs by FLIM is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Numerous materials have been identified that can inhibit insulin fibrillation, such as protein-based molecular chaperone, 13 peptide, 14 green tea polyphenol, 15 curcumin, 16 metal ion chelator, 17 nanoparticle, 18 chemical chaperones, 19 etc., but most of these inhibitors suffer from the lack of flexibility in different applications. 20 So far researchers have identified that materials having hydrophobic, polar, or electrostatic properties act as effective inhibitors, 21,22 and polymer-based inhibitors gained increasing interest due to their multifaceted advantages over myriads of bio-applications. 23,24 Since hydrophobic and polar interactions play a crucial role during fibril inhibition, we became interested to take advantage of hydrophobic polyisobutylene (PIB) and polar sugar moieties in a single macromolecular design.…”
Section: Introductionmentioning
confidence: 99%